(untitled) (Journal of Educational Sciences, 2024)
The present research is a mixed method study aimed at exploring the current state of the usage of English as a Lingua Franca in the Kazakhstani healthcare settings and international advancements in teaching English for medical purposes. To reach this goal we employed both quantitative (survey) and qualitative (systematic review) research methods. An anonymous self-administered survey was conducted among potential English-speaking patients currently studying or residing in Kazakhstan (n = 44). It was revealed that a significant number of patients commonly visited hospitals for minor illnesses (e.g., cold, flu), routine check-ups, and obtaining medical certificates, but many of them experienced unclear communication. In the systematic review conducted according to PRISMA guidelines, 12 articles were selected for final analysis, revealing effective teaching innovations in teaching English to medical students that improve language skills and academic performance. Namely, several trends were identified across reviewed studies such as technology-enhanced learning (microblogging-based instruction, metaverse environments, blended teaching), collaborative and peer-assisted learning (peer-feedback, involving international students in peer-teaching) and various interactive and engaging methods. The findings of this study can assist Kazakhstani educators and methodologists in staying updated with teaching innovations implemented by international counterparts. This knowledge can be used to integrate effective practices into English teaching syllabuses for medical students. Understanding patients’ experiences can enhance teachers’ awareness of the communication challenges faced by English-speaking patients in healthcare settings and the most common scenarios in doctor-patient communication. This awareness can facilitate teachers in tailoring their instructions to better prepare medical students for real-world communication in healthcare contexts. Key words: English for special purposes, MELF, medical students, doctor-patient communication.